Tardive dyskinesia in patients treated with atypical antipsychotics: case series and brief review of etiologic and treatment considerations - Jungjin Kim; Eric MacMaster; Thomas L Schwartz (BioExcel Publishing Ltd, 2014)
Tardive dyskinesia (TD) is a disfiguring side-effect of antipsychotic medications that is potentially irreversible in affected patients. Newer atypical antipsychotics are felt by many to have a lower risk of TD. As a result, many clinicians may have developed a false sense of security when prescribing these medications. We report five cases of patients taking atypical antipsychotics who developed TD, review the risk of TD, its potential etiologic mechanisms, and treatment options available. The goal of this paper is to alert the reader to continue to be diligent in obtaining informed consent and monitoring for the onset of TD in patients taking atypical antipsychotics.